(untitled) (Acta Scientiarum. Animal Sciences, 2020)
The current study investigated the effect of dietary supplementation with probiotics and Yucca schidigera extract on physicochemical parameters, proximate composition, mineral content and fatty acid profile of broiler breast and thigh muscles. In total, 240 one-day old broilers were randomly allocated into two dietary treatments groups: 1) Control (basal diet), 2) experimental (basal diet with two probiotics Pediococcus acidilactici and Saccharomyces cerevisiae and Yucca schidigera extract). The results showed that the pH value was higher in the experimental group than in the control group (p < 0.05). However, drip, cook and thaw losses were not influenced by dietary treatment (p > 0.05). A significant increase in protein, Fe, Zn, Na, P and a significant decrease in lipid, Cu and Cr contents was exhibited in experimental group relative to control group (p < 0.05). The proportion of stearic acid and saturated fatty acids was significantly (p < 0.05) reduced, whereas linoleic acid and polyunsaturated fatty acids contents were significantly (p < 0.05) increased in breast and thigh muscles of fed the experimental diet. We concluded that additive supplementation of the diet with probiotics and Yucca schidigera extract could improve meat quality.